Superdotación intelectual y trastorno por déficit de atención e hiperactividad (TDAH) - Pardo de Santayana Sanz, Raquel (FAISCA: Journal of High Abilities, 2002)
Gifted children with AD/HD (Attention Deficit Hyperactivity Disorder) differ from average children with AD/HD and from gifted children without this disorder in diverse ways that impact assessment of both (giftedness and AD/HD). Nowadays educators do not seem to have strategies nor confidence in providing an appropriate curriculum for these children. The article exposes this issue reviewing this population’s reality among their family and school environment, drawing some ideas for their education.